Đứt gãy đang hoạt động và động đất cực đại đới đứt gãy Sông Hồng khu vực Lào Cai - Yên Bái - Liêm, Ngô Văn; Trịnh, Phan Trọng; Vinh, Hoàng Quang (Vietnam Journal of Earth Sciences, 2018)
The active faults and the maximum earthquakes of the Red River fault zone in Lao Gai - Yen Bai area